Stages of the ongoing global financial crisis: Is there a wandering asset-price bubble? - Lucjan T. Orlowski (Center for Social and Economic Research (CASE), 2008)
This study identifies five distinctive stages of the current global financial crisis: the meltdown of the subprime mortgage market, spillovers into broader credit market, the liquidity crisis epitomized by the fallout of Northern Rock, Bear Stearns with contagion effects on other financial institutions, the commodity price bubble, and the ultimate demise of investment banking in the U.S. Monetary policy responses aimed at stabilizing financial markets are proposed. The study argues that the severity of the crisis is influenced strongly by changeable allocations of global savings, which lead to over-pricing of varied types of assets. The study calls such process a wandering asset-price bubble”. Unstable allocations have elevated market, credit and liquidity risks. Since its original outbreak induced by the demise of the subprime mortgage market and the mortgage-backed securities in the U.S., the crisis has reverberated across other credit areas, structured financial products and global financial institutions.
Keywords: G12; G15; G21; G24; 330; subprime mortgage crisis; credit crisis; liquidity crisis; market risk; credit risk; default risk; Level 3 assets; Basel II; Finanzkrise; Vermögen; Spekulationsblase; Spillover-Effekt; Ansteckungseffekt; Hypothek; Kreditmarkt; Geldmarkt; Kreditwürdigkeit; Bankenaufsicht; Welt